Cycling performance tips or optimizing personal athletic performance - Rafoth, D. (2005)
Our inherited abilities (genes) set the ultimate limit for our personal athletic performance. But it is our training and nutritional programs that more commonly make the difference when setting a personal best or winning an event. It is not unusual to see the advantages of nutritional supplements and training aids based on anecdotal (rather than scientific) evidence with the sponsor benefiting financially from their use.